The Difference of Bullet Marks on Metal Sheets from FMJ, JHP and LRN Bullets - รัตนพันธ์ มนต์ทิชา (Journal of Food Health and Bioenvironmental Science, 2017)
The purpose of this research was to study the pattern and the difference of marks on the metal door car caused by the collision of gunshots using FMJ (Full Metal Jacket), JHP (Jacketed Hollow Point) and LRN (Lead Round Nose), shot from a 9 mm Glock automatic pistol at the different distances. This research methodology was experimental. In this experiment, the metal sheets were from a Chevrolet sedan in two measuring 30 x 30 x 0.12 cm. The gun used in this research was a Glock 19 9 mm semi-automatic pistol. The shooting assessment tested three different distances. The images of bullet marks on the metal sheets were recorded by digital camera. The width, length and depth of bullet marks were measured by the digital vernier caliper and the obtained data were statistically analyzed. The results revealed that the sizes of bullet marks on the metal sheets caused by JHP (Jacketed Hollow Point) were larger than the bullet marks from FMJ (Full Metal Jacket) and LRN (Lead Round Nose). However, the distance of shooting had no effect to the average width and length of bullet marks; the kind of bullet of shot affected the average of width and length of bullet marks (at the significant level of 0.05).